The Physical Growth of Liza aurata (Risso,1810) Reared in Marine Earth Ponds (Latakia University Journal -Biological Sciences Series, 2023)
Our current study aimed to know the physical development of Golden grey mullet, Liza aurata, which reared in marine ponds located near Al Hossain River estuary in Tartous.Diet containing 25% protein were provided.This experiments started from August 2021 till November 2022. Liza aurata fingerlings, caught from the marine water opposite the Alhussein River estuary, were distributed into a breeding pond which was divided by silk nets into three parts with a density of 300 fingerling/part, and fed twice a day. Hydrological parameters of the water were taken daily and the averages of fish weight and length measurements were taken monthly. Service operations were performed periodically.The results showed that the average monthly weight increased during summer in the three groups, and tends to be better for the third group with the largest primary average weights (23.66(g. Average weight for the three groups during the spring, summer and autumn seasons was respectively as follows: (15.2, 41.2 , 85.27(g for the third group, (9.9, 33.53, 73.57(g for the second group, and (7.67, 30.4, 64.6(g for the first group.Additionally, the feed conversion ratios during spring and summer for the three groups were:(1.88, 1.75), (1.94, 1.74), and (2.41, 2.3) respectively.